A Subaltern Reading of International Organisations and Issues of Order, Disorder and Marginality. (March 2014) - Singh, Surabhi; Basu, Moushumi
The article draws on Bourdieu's notion of orthodoxy and doxa, whereby a particular view of the world becomes established as a normal, natural and unquestioned truth, as the entry point for the discussion on international organisations and issues of order, disorder and marginality. Every established order, according to Bourdieu, tends to produce very different degrees and with very different means, the naturalisation of its own arbitrariness, whereby it successfully manages to make the world conform to the myth of it being a self-evident and natural order. Such a project as the article argues, given the very constitution of international society is highly problematic, especially from the standpoint of those traditionally located at the very margins of decision making—the subalterns. In deconstructing the meaning and substance of 'order' through select case studies, the article seeks to explicitly focus on international organisations as sites of power and control, the processes of institutionalisation and socialisation and the possibilities of change that posit new ways of thinking about issues of order and disorder in international relations.